Android-Based Selling Point and Animal Care Information System (Vet Clinic) In A Company Operating in The Field of Technology Services and Pet Care and Basic Needs in Cianjur Regency - Nisa Syifa Muzahidah; Ahfi Fauka Pranata; Nono Sudarsono; Roni Ilham Subagja (Journal of Economics, Management, and Entrepreneurship, 2025)
The prior technology allowed clients to view only available products, without providing functionality for direct payments and service orders through the application. Users were limited to browsing a catalog of products, such as food, accessories, and pet pharmaceuticals. However, they were required to visit the store in person to acquire items or request services such as grooming, health assessments, and pet boarding. This constraint rendered the transaction process inefficient and curtailed consumer convenience. The absence of online payment options restricted clients' flexibility in selecting payment methods that met their preferences, such as bank transfers or cash-on-delivery (COD). This research develops an information system that facilitates direct ordering and payment through the application, thereby overcoming these limitations. These new capabilities enable users to effortlessly order services such as grooming, pet boarding, or health assessments, in addition to acquiring necessary items. The application accommodates various payment options, including bank transfers and cash on delivery, providing considerable flexibility for consumers. This application is developed using the Flutter framework for the frontend, ensuring a responsive and visually appealing user experience, and CodeIgniter for the backend, which manages server functionality and data handling. Through these changes, a technological services and vital pet care firm in Cianjur aims to attract additional customers, enhance its sales potential, improve customer satisfaction, and expand its market share in Cianjur and surrounding regions